PENGARUH BYSTANDER EFFECT, WHISTLEBLOWING, DAN PERILAKU ETIS TERHADAP FINANCIAL STATEMENT FRAUD - Maharani -; Hadi Mahmudah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
In an organization or company, fraud is usually discovered by people within the organization. The existence of evidence of fraud, whether strong or weak, sometimes does not make people who know the fraud report to the authorities. The purpose of this study was to determine the effect of the bystander effect, whistleblowing, and ethical behavior on financial statement fraud. The method used is a quantitative method. The population in this study were all Bekasi District Civil Servants who served in the financial division of each agency. This study uses primary data from a questionnaire. The data were analyzed using multiple regression analysis. The results of this study indicate that the bystander effect has a positive effect on Financial Statement Fraud, while the whistleblowing variable and eris behavior have a negative effect on Financial Statement Fraud.